Simulation models for tankless gas water heaters - Quintã, André F. (2019)
There is a growing concern about to the scarceness of natural resources and the emissions problematic. Water heating is a relevant part of a household’s energy use, and tankless gas water heaters (TGWH) are widely used. There are design and engineering challenges to develop more efficient devices, with lower emissions of pollutant gases and providing comfort improvements from the user point of view. The main objective of the present work is to provide mathematical models to evaluate and support the development of different TGWH configurations. By simulation, different hardware configurations and advanced control strategies can be tested and optimized regarding energy saving, reducing of harmful environmental emissions and increase of comfort indices by reducing temperature undershoots and overshoots. The TGWH individual components are modelled, laboratory tests are performed and the heat cell is parametrized with experimental data. Configurations with and without bypass function are performed for several water flow rates and setpoint temperature patterns in open loop and with feed-forward control.